Penyelesaian Rangkaian Listrik Menggunakan Invers dan Eliminasi Gauss Berdasarkan MATLAB - Ulul Ilmi; Zaenal Abidin; M. Lais Shofil Muna; Muhammad Aflah Kafabi; Nafik Burhanudin; Ahmad Faizin; Faried Nur Imanudin; Mudafiqil Ilmi (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Solving electrical circuits often requires finding solutions to systems of linear equations, which are derived from fundamental laws like The laws of Kirchhoff and Ohm's law. In this study, two widely known numerical methods are used to solve these systems, Gaussian elimination and matrix inversion. Both methods are applied to the linear equations that represent the electrical circuit network. MATLAB is used to model and solve the circuits with these techniques, making the calculations more efficient and accurate. By employing both methods, we can solve systems of equations for various circuit configurations, determining the voltage and current values for each component. The results demonstrate that both methods are reliable and fast, providing valuable insights for electrical engineering and circuit analysis.